Synchronization of Two Spin-Transfer-Driven Nano-Oscillators Coupled Via Magnetostatic Fields - Altbir-Drullinsky, D; Allende-Prieto, S; Mancilla-Almonacid, D (American Physical Society, 2019)
The magnetization dynamics of nano-oscillators may be excited by both magnetic fields and spin-polarized currents. While the dynamics of single oscillators has been well characterized, the synchronization of several ones is not fully understood yet. An analytical and numerical study of the nonlinear dynamics of two magnetostatically coupled spin valves driven by spin-transfer torques is presented under the macrospin approximation. The oscillators interact via magnetostatic fields and exhibit a robust synchronized magnetization motion. We describe the magnetization dynamics of the system using the Landau-Lifshitz-Gilbert-Slonczewski equation. Using a modal decomposition technique, we describe the dynamics, synchronization, and competition of oscillatory modes as a function of the current density, and the geometrical parameters of the setup. Simulations of the Landau-Lifshitz-Gilbert-Slonczewski equation show good agreement with an approximate analytic solution. © 2019 American Physical Society.